Pengaruh Work Life Balance dan Perceived Organizational Support terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening (Studi Kasus pada PT Primaplast Indonesia) - Shahnaz Mawaria Zahra; Wawan Prahiawan (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the effect of work-life balance and perceived organizational support on employee performance, with job satisfaction serving as an intervening variable at PT Primaplast Indonesia. This study employed a quantitative approach using a survey method. The population consisted of 81 employees of PT Primaplast Indonesia, and a saturated sampling technique was applied, allowing all population members to participate as respondents. Data were collected through questionnaires and analyzed using SmartPLS-based Structural Equation Modeling (SEM). The findings indicate that work-life balance and perceived organizational support have a positive and significant effect on both employee performance and job satisfaction. Job satisfaction also has a positive and significant effect on employee performance. Furthermore, job satisfaction positively and significantly mediates the relationship between work-life balance and employee performance, as well as the relationship between perceived organizational support and employee performance.